A growing dilemma of tourism diffusion and sustainability: Wows and woes for Bangladesh eco-tourism - Muhammad Shoeb-Ur-Rahman; Rokeya Binte Shahid (UTMS Journal of Economics, 2012)
Tourism is one of the emerging and fastest growing industries in the world today. It is well said that every twelve tourists creates a new job. Current study discusses the diffusive nature of tourism that demands an inclusion of the concept 'sustainability' which in turn creates the impression for 'ecotourism'. Afterward the study tries to find out ecotourism possibility to explore and potential challenges with special context of Bangladesh tourism industry. The concept of ecotourism adds the concern for environment as well as socio-economic status. Ecotourism must be promoted for sustainable development by establishing a durable productive base that allows the local inhabitants and ecotourism service providers to enjoy rising standards of living and environmental conservation. This paper provides an idea of how different tourism destinations, especially ecotourism become an effective tool for the sustainable development in Bangladesh. Secondary data were used to address the objectives in this study. However, some marketing strategies are pointed out as recommendations based on which several action programs could be taken for establishing as well as standardizing Bangladesh as an eye-catching ecotourism destination.
Keywords: L83; N55; O13; 330; tourism diffusion; sustainability; eco-tourism; Bangladesh; wows; woes